DETERMINANT FACTORS ON THE FINANCIAL STATEMENTS DISCLOSURE IN INDONESIAN LOCAL GOVERNMENT - khoirul aswar (Jurnal Studi Akuntansi Pajak Keuangan, 2024)
In this study we explore the relationship of the number of local parliamentarians (NUMPAR), local government budget expenditure (BUDEX), java / non-java jurisdiction (JAVANON) and presence of an assistance and training program (ASSTPROG) with financial statement disclosure. It relies on multiple theoretical frameworks and uses a sample of 40 local government financial reports in Java and in Sumatra island in 2020 which had been audited by the Indonesian National Audit Board (BPK RI). We found java / non-java jurisdiction and presence of an assistance and training program affect the disclosure of financial statements. In addition, the number of local parliamentarians and local government budget expenditure does not affect the disclosure of financial statements. The contribution to local government is to analyze potential aspects related to the government's increased pressure to make financial statement disclosures. One of the ways for regional governments to carry out financial statement disclosures is to employ information technology to meet social needs in a more efficient and effective manner.